ENCOURAGING CRITICAL LITERACY DEVELOPMENT THROUGH EXTENSIVE READING ACTIVITY IN AN EFL (ENGLISH AS A FOREIGN LANGUAGE) CONTEXT - Asanti, Chris; Syamdianita, Syamdianita (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2017)
This study is an attempt to address the issue of how extensive reading (ER) as a supplementary reading approach is able to encourage students’ critical literacy. Further, how ER influences students’ perception of critical literacy related to students’ viewpoint of the texts is examined thoroughly. ER in this study was employed as a supplementary reading activity where students were engaged to read in a large number of materials on a wide range of topics and they had freedom to select the reading material based on its relevance to their interests, knowledge, and experience (Day & Bamford, 2002). Relating the characteristics of ER, it seemed to us that students’ understanding of the text through ER activity should be scrutinized as one important aspect in English language teaching (ELT). In order to get more comprehensive picture, questionnaires were distributed to 38 students in the class. Yet, only 3 (three) students were willing to return the questionnaire and to be interviewed based on their answers in the questionnaire. The findings revealed that ER is evidenced to motivate students to approach texts critically, challenge taken knowledge, relate the texts to world’s issues, improve their awareness of how to see and understand human beings, and question the intention of the texts from distinct viewpoints.Keywords: extensive reading, critical literacy development, EFL